PENGARUH AUDIT TENUR DAN UKURAN PERUSAHAAN TERHADAP INTEGRITAS LAPORAN KEUANGAN DENGAN KUALITAS AUDIT SEBAGAI VARIABEL INTERVENING (Studi Pada Perusahaan Real Estate dan Property Yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2015) - Shofi Aulia Rahman, 13.05.52.0207; Himmawan, Arief (Students Journal of Accounting and Banking, 2018)
This study aims obtain empirical evidence about the influence of tenure audit and firm size to integrity of financial statements with audit quality as intervening variable at real estate and property companies which listed in the Indonesia Stock Exchange. The population on this research is all real estate and property company in the Indonesia Stock Exchange in 2013 - 2015. The sampling technique used was purposive sampling. The analytical tool was used is Multiple Regression Analysis. Partial results of this study show the Tenure Audit have no efect significant on Integrity of Financial Statements, Firm Size significant with Integrity of Financial Statements, Audit Quality significant with Integrity of Financial Statements, Tenure Audit have no efect significant on Audit Quality, and Firm Size significant on Audit Quality.Keywords : tenure audit, firm size, audit quality and integrity of financial statments